Controller design for analgesia with quantized pupil size variation output and saturating infusion rate. Issue 18 (2016) - Zabi, Said; Queinnec, Isabelle; Tarbouriech, Sophie; Mazerolles, Michel
Abstract: This paper proposes a strategy for the design of a dynamic output-feedback controller for analgesia taking into account the saturation of the input and the quantization of the output. Besides that, the design of this controller takes into account the multiple time scale dynamics in the analgesia model, accelerates the fast dynamics and establishes global stability. The control design is cast into a two-step strategy. The controller is first designed for the fast system and the stability analysis is then performed on the full model to evaluate domains of safe behavior.